What's that garage for? Private parking and on-street parking in a high-density urban residential neighbourhood. (May 2020) - Scheiner, Joachim; Faust, Nico; Helmer, Johannes; Straub, Michael; Holz-Rau, Christian
Abstract: High-density inner-city residential neighbourhoods are often characterised by serious parking pressure and illegal parking. We study parking choices in a historical neighbourhood in Dortmund, Germany, using a household survey. Specifically, we look at the availability of and distance to private parking, the use of available private and on-street parking, and search duration. Additionally, we look at simple measures of satisfaction with parking and with the neighbourhood in general. Our results show that available private parking is not necessarily used where there is little control of illegal on-street parking. Furthermore, search durations and distance to cars parked on-street suggest that parking pressure is lower than commonly perceived in the neighbourhood. Private parking is under-utilised to the extent that we estimate that illegal parking can be reduced by 28 to 49% if private parking were consistently used by those who have it available. Even more substantial reductions in illegal parking can be achieved by deviating from standard sizes for public parking spaces. From our results we draw conclusions for urban parking policy. These include introducing parking fees, coupled with paid parking permits for residents and, perhaps, employees; defining short-stay parking zones; providing parking spaces of different sizes; and increasing the level of enforcement.